2016
DOI: 10.1002/dc.23508
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid lesions: Difficult diagnosis on cytology

Abstract: Cytology of parathyroid lesion (PL) is often confused with that of thyroid lesions. Differentiation between thyroid and PL is very difficult on cytomorphology because of their similar features and close anatomical proximity. Three cases of PLs reported on cytology in last one year were retrieved from archives of cytology department. Their cytomorphological details were studied and were correlated with the available biochemical parameters. Histopathology was available in two cases. Radiological assistance and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Nuclear overlapping and nuclear molding, which are uncommon findings in benign thyroid aspirates, also were reported as findings in parathyroid aspirates . One case series also found similar features . Dimashkieh and Krishnamurthy reported that nuclei measuring smaller than thyroid follicular cells, bare nuclei, stippled chromatin, and a prominent vascular network with adherent cells indicated parathyroid origin .…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Nuclear overlapping and nuclear molding, which are uncommon findings in benign thyroid aspirates, also were reported as findings in parathyroid aspirates . One case series also found similar features . Dimashkieh and Krishnamurthy reported that nuclei measuring smaller than thyroid follicular cells, bare nuclei, stippled chromatin, and a prominent vascular network with adherent cells indicated parathyroid origin .…”
Section: Introductionmentioning
confidence: 76%
“…Common major cytomorphologic features of parathyroid tissue that have been reported in the literature include a papillary-like pattern with fibrovascular cores or prominent vascular network/proliferation, stippled chromatin, follicular pattern, and bare nuclei (Table 5). 2,[4][5][6][7][8][9][18][19][20][21][22] The majority of these studies also concluded that a combination of cytomorphologic features supported by either ancillary studies or correlation with clinical, radiologic, and laboratory findings are important in establishing a correct diagnosis of parathyroid tissue. The main diagnostic features in the current study also included bare nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were submitted as a thyroid nodule FNA, and represented 0.12% of the total thyroid FNAs examined over this period. Using previously published criteria, 47 samples (78%) displayed cytologic findings that were suggestive of PT cells, and were subsequently confirmed with IHC. Thirteen (13) samples (22%) had cytologic features that were not recognized as PT on initial ThinPrep evaluation and were classified using TBSRTC criteria as either AUS or SFN.…”
Section: Resultsmentioning
confidence: 98%
“…The cytologic features of parathyroid (PT) cells have been well described, both in conventional smears and in liquid‐based preparations . However, ectopic PT within the thyroid gland can be difficult to recognize, as both are neuroendocrine glands and show similar cytologic features .…”
Section: Introductionmentioning
confidence: 99%